A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea) - Anker, Arthur (Zootaxa, 2020)
A new alpheid shrimp genus, Pachelpheus gen. nov., is established to accommodate Pachelpheus pachyacanthus sp. nov., described based on two specimens from the Las Perlas Archipelago, Pacific coast of Panama. Pachelpheus pachyacanthus sp. nov. appears to be an obligate symbiont dwelling in burrows of yet unknown infaunal hosts, on shallow near-shore subtidal sand flats. The main morphological characters of Pachelpheus gen. nov. are: (1) frontal margin of carapace with broadly rounded rostral projection, without orbital teeth; (2) sixth pleonite with articulated plate; (3) telson with two pairs of cuspidate setae dorsally, without anal tubercles; (4) eyes concealed in dorsal view, partly visible in lateral view; (5) chelipeds equal in size, symmetrical in shape, moderately enlarged, stout, carried extended; (6) cheliped carpus without rows of setae mesially; (7) cheliped fingers without snapping mechanism, each finger armed with one stout tooth; (8) second pereiopod carpus with five sub-articles; (9) third, fourth and fifth pereiopods with ischia armed with single robust cuspidate seta, meri armed with one to several unusually robust cuspidate setae; (10) second pleopod with appendix masculina in males only; (11) uropodal exopod and endopod with rows of slender spiniform setae on their distal margins; (12) uropodal diaeresis unusually thickened laterally, with two very stout spiniform setae; and (13) lateral lobe of the uropodal protopod rounded. The new genus appears to be morphologically most similar to Jengalpheops Anker & Dworschak, 2007 and Leslibetaeus Anker, Poddoubtchenko & Wehrtmann, 2006.